EXPLORING THE USE OF SOCIAL MEDIA FOR LEARNING SPEAKING BY THE ELEVENTH GRADE STUDENTS OF SMAN 3 KEDIRI - Siti Nur Khofifah; Ary Setya Budhi Ningrum; Annisa Auliya Saharani (Magister Scientiae, 2023)
The purpose of this study is to investigate the use of social media for learning to speak, as well as the challenges and motivations for doing so. The subject of this study is the eleventh grade students of SMAN 3 Kediri, which is located on Mauni Street, No. 88 Bangsal, Pesantren, Kediri City. Data collection methods include questionnaires, observation, and interviews. Data analysis processes included data reduction, data organization, and data conclusion. The obtained data is displayed descriptively as a percentage and qualitatively interpreted. The data showed that all participants use social media as a source of knowledge and as an example of practicing speaking. 59% of the 80 participants agreed and 24% strongly agreed that social media can help them improve their speaking fluency. The students also claim that learning to speak through social media presents challenges. Understanding difficult material without the assistance of teachers is one of the most difficult aspects for students. The findings also show that the motivation for using social media to learn to speak comes from both internal and external sources. Furthermore, students can use social media to learn to speak in a variety of ways, and it also provides challenges and motivation for each student.